Aberrant Development and Synaptic Transmission of Cerebellar Cortex in a VPA Induced Mouse Autism Model - Wang, Ruanna; Tan, Jiahui; Guo, Junxiu; Zheng, Yuhan; Han, Qing; So, Kwok-Fai; Yu, Jiandong; Zhang, Li (Frontiers in Cellular Neuroscience, 2018)
Autistic spectral disorder (ASD) is a prevalent neurodevelopmental disease that affects multiple brain regions. Both clinical and animal studies have revealed the possible involvement of the cerebellum in ASD pathology. In this study, we generated a rodent ASD model through a single prenatal administration of valproic acid (VPA) into pregnant mice, followed by cerebellar morphological and functional studies of the offspring. Behavioral studies showed that VPA exposure led to retardation of critical motor reflexes in juveniles and impaired learning in a tone-conditioned complex motor task in adults. These behavioral phenotypes were associated with premature migration and excess apoptosis of the granular cell (GC) precursor in the cerebellar cortex during the early postnatal period, and the decreased cell density and impaired dendritic arborization of the Purkinje neurons. On acute cerebellar slices, suppressed synaptic transmission of the Purkinje cells were reported in the VPA-treated mice. In summary, converging evidence from anatomical, electrophysiological and behavioral abnormalities in the VPA-treated mice suggest cerebellar pathology in ASD and indicate the potential values of motor dysfunction in the early diagnosis of ASD.